Observation of A1g Raman mode splitting in few layer black phosphorus encapsulated with hexagonal boron nitride. Issue 48 (1st December 2017) - Urban, J. M.; Baranowski, M.; Surrente, A.; Wlodarczyk, D.; Suchocki, A.; Long, G.; Wang, Y.; Klopotowski, L.; Wang, N.; Maude, D. K.; Plochocka, P.
Abstract : We observed a predicted but elusive Raman peak in hBN-encapsulated black phosphorus on the high wavenumber side of A1g. Abstract : We investigate the impact of encapsulation with hexagonal boron nitride (h-BN) on the Raman spectrum of few layer black phosphorus. The encapsulation results in a significant reduction of the line width of the Raman modes of black phosphorus, due to a reduced phonon scattering rate. We observe a so far elusive peak in the Raman spectra ∼4 cm −1 above the A1g mode in trilayer and thicker flakes, which had not been observed experimentally. The newly observed mode originates from the strong black phosphorus inter-layer interaction, which induces a hardening of the surface atom vibration with respect to the corresponding modes of the inner layers. The observation of this mode suggests a significant impact of h-BN encapsulation on the properties of black phosphorus and can serve as an indicator of the quality of its surface.